Achieving Enhanced Photochromic Properties of Diarylethene through Host‐Guest Interaction in Aqueous Solution. Issue 65 (13th October 2021) - Sun, Dongdong; Wu, Yong; Han, Xie; Liu, Simin
Abstract: Diarylethene (DTE) has been widely used in fluorescence probes, molecular logic gates, optical data‐storage devices owing to the excellent photochromic property, while constructing high‐performance photochromic DTE in aqueous media remains a big challenge. Herein we present several host‐guest systems formed between cucurbit[ n ]uril (CB[ n ], n =7, 8, 10) and two water‐soluble DTE derivatives 1 and 2 . It was found that host‐guest interactions not only affect the photophysical properties of photochromic guests, but also make great differences on the photoreaction process. Different host‐guest binding behaviors also lead to different effects on the photochromic properties of guests. In the presence of CB[ n ], both 1 and 2 showed enhanced emission and higher fluorescence quenching ratio at photostationary state. Besides, CB[10]⋅1 exhibited faster response rate in cyclization reaction and better photofatigue resistance than free 1 in aqueous solution, while the supramolecular assembly of (CB[8])n ⋅ (2 )n showed slower response rate in both directions of the reversible photoreaction. Besides, the photofatigue resistance of 2 can be greatly improved through binding with CB[7]. Our results suggest that host‐guest interactions could be an efficient way to improve photochromic properties of DTE in aqueous solution. Abstract : In the presence of CB[ n ] host, the photophysical and photochemical properties of diarylethene derivatives (DTEs) were significantly affected. With suitable CB[ n ], DTEs showed faster response rate, better fatigue resistance, and higher fluorescence quenching ratio, suggesting that high‐performance photochromic system in aqueous solution can be constructed through CB[ n ]‐based host‐guest interactions.